Copper and l-(−)-quebrachitol catalyzed hydroxylation and amination of aryl halides under air. Issue 33 (13th August 2020) - Liang, Xinjie; Li, Hui; Du, Fangyu; Zhang, Yongsheng; Dong, Jinhua; Bao, Xuefei; Wu, Ying; Chen, Guoliang
Graphical abstract: Highlights: New application of l -quebrachitol. A green method for hydroxylation and amination of aryl halides was developed. 100 g-scale synthesis. Abstract: l -(−)-Quebrachitol, a natural product obtained from waste water of the rubber industry, was utilized as an efficient ligand for the copper-catalyzed hydroxylation and amination of aryl halides to selectively give phenols and aryl amines in water or 95% ethanol. In addition, the hydroxylation of 2-chloro-4-hydroxybenzoic acid was validated on a 100-g scale under air.